Stimuli‐Driven Insulator–Conductor Transition in a Flexible Polymer Composite Enabled by Biphasic Liquid Metal (Adv. Mater. 43/2021). Issue 43 (25th October 2021) - Liu, Huaizhi; Xin, Yumeng; Bisoyi, Hari Krishna; Peng, Yan; Zhang, Jiuyang; Li, Quan
Abstract : Metal–Polymer Composite In article number 2104634, Jiuyang Zhang, Quan Li, and co‐workers report a fascinating binary metal–polymer composite that can have a stimuli‐driven transition from a biphasic to a monophasic state of liquid metals. The composite has applications toward next‐generation soft electronics.